Towards harmonised balance of payments and international investment position statistics – the experience of the European compilers - Jean Marc Israël; Carlos Sánchez Mu\~noz (European Central Bank (ECB), 2007)
External statistics – specifically balance of payments and international investment position statistics – are among the primary statistics on which policy-making bodies and markets rely as a basis for their decisions in globalised economies. Monitoring and enhancing data quality in the context of rapidly changing economies impose heavy constraints on compilers of these statistics. As it becomes increasingly important worldwide to adhere to a set of international statistical standards in order to ensure the comparability of statistics, the elaboration of meaningful EU/ euro area aggregates hinges critically on attaining a high degree of homogeneity across countries' contributions. In addition to offering their own value for analysis, the euro area external statistics are the main source for the compilation of the rest-of-the-world account in the quarterly euro area (financial and nonfinancial) accounts. Bearing this in mind, a lot has been achieved since the inception of the euro area to harmonise concepts and definitions in line with international statistical standards, to review the data collection and compilation systems, as well as to enhance the overall data quality. However, asymmetries1 both across euro area countries and with counterparts elsewhere still need to be overcome. Additionally, new challenges lie ahead for compilers of statistics, with the steady process of globalisation and the increasing role of financial innovation (in terms of both new instruments and new institutional vehicles) observed in financial markets. While the compilation of euro area statistics continues to be based on country contributions, which are mostly derived from national collection systems in accordance with the principle of subsidiarity, common tools are built up and maintained by the European Central Bank and national compilers. In particular, the Centralised Securities Database is playing a pivotal role in the move towards security-by-security reporting and should greatly enhance the quality of security-related information, i.e. portfolio investment flows, stocks and income. The tremendous work of European statisticians towards producing harmonised euro area statistics that are fit for purpose has also benefited statisticians elsewhere and is playing an important role in the current updating of international standards (the 1993 System of National Accounts and the International Monetary Fund's Balance of Payments Manual, fifth edition). Statisticians have worked in close cooperation in various European fora to clarify concepts and identify best practices with a view to enhancing data quality and reducing the reporting burden. This paper aims to make this experience widely available.
Keywords: 330; Zahlungsbilanzstatistik; Auslandsinvestition; Statistik; EU-Staaten